(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the problems of conservation of archaeological heritage objects. It tried to show the process of conservation of archaeological heritage objects carried out in our country until now, as well as the achievements and shortcomings related to them. First of all, surveys conducted in Poland to study the attitude of the population towards cultural heritage objects were analyzed. In particular, it has been shown that the level of awareness of archaeological heritage among the population is very low even in European countries, which are developed countries, and in us it is in a worse state. Against the background of rapid development of tourism in Uzbekistan in the following years, attention is paid to the works planned to be implemented on the basis of a number of decisions taken by our government in order to protect and preserve archaeological heritage objects and turn them into museum objects. During the years of independence, several efforts have been made to conserve archaeological heritage sites, and it will be considered that they were carried out in different years and in different ways. The conservation and styles of archaeological heritage objects such as Afrosiyob walls, Fayoztepa, Aksaroy, ancient bath in Samarkand, Shahrisabz bath, Mingurik and Ahsikent are analyzed.